Extractive resource industries and indigenous community-based monitoring: Cooperation or cooptation?. Issue 4 (November 2020) - Natcher, David C.; Brunet, Nicolas D.
Highlights: ICBM presents opportunities and challenges in the management of resource extraction. ICBM is embedded within complex socio-cultural and political contexts that must be considered in its design and implementation. ICBM can support self-determination and indigenous nationhood. ICBM can be used by corporate and settler institutions to advance their agendas in the resource sectors. Abstract: This special issue is an interdisciplinary collection of papers that explores the many dimensions of Indigenous community-based monitoring (ICBM). The focus is on areas/sites in Canada, and to a lesser extent internationally, where Indigenous peoples have assumed a role in the monitoring of industrial activities. This collection provides the reader with an understanding of the current status and effectiveness of ICBM in advancing the territorial rights and interests of Indigenous peoples. Themes explored include ICBM contributions to Indigenous self-determination, jurisdictional and the politics of exclusion, issues regarding gender and racial identity, the roles of science and Indigenous knowledge within these efforts as well methods to sustain and implement strategies derived from ICBM programs such as impact and benefit agreements.